Comparison of Different Formulations for the Numerical Calculation of Unsteady Incompressible Viscoelastic Fluid Flow (Advances in Applied Mathematics and Mechanics, 2019)
In this paper we compare different methods currently used in the stabilization of numerical simulations of time-dependentviscoelastic fluid flows described with the Oldroyd-B and relatedmodels. The methods under consideration, based on the separation ofnewtonian-like components from the stress tensor, are applied to afinite volume analysis of two simple benchmark problems (the planePoiseuille startup and pulsated flows), for which analyticalsolutions are known. The relative performances of each method areevaluated regarding stability, accuracy and efficiency.